2022
DOI: 10.1371/journal.pone.0275879
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and recurrence of cause-specific postpartum hemorrhage: A population-based study

Abstract: Objective To explore risk profiles of the different types of postpartum hemorrhage (PPH >500ml or severe PPH >1500ml) and their recurrence risks in a subsequent delivery. Methods With data from The Medical Birth Registry of Norway and Statistics Norway we performed a population-based cohort study including all singleton deliveries in Norway from 1967–2017. Multilevel logistic regression was used to calculate odds ratio (OR), with 95% confidence interval (CI), with different PPH types (PPH >500ml or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(89 reference statements)
2
4
0
1
Order By: Relevance
“…This is in line with the findings of Oberg et al, who found an overall increased risk of the recurrence of postpartum haemorrhage across all haemorrhage subtypes 9 . However, it is in contrast with the findings of Linde et al, who found significant differences in the recurrence risk for postpartum haemorrhage, where the strongest risk for recurrence was found for dystocia, retained placenta and atony 8 . It should be stated that many of these diagnoses are interconnected, and that medical coding may not fully reflect the complexity of a postpartum haemorrhage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with the findings of Oberg et al, who found an overall increased risk of the recurrence of postpartum haemorrhage across all haemorrhage subtypes 9 . However, it is in contrast with the findings of Linde et al, who found significant differences in the recurrence risk for postpartum haemorrhage, where the strongest risk for recurrence was found for dystocia, retained placenta and atony 8 . It should be stated that many of these diagnoses are interconnected, and that medical coding may not fully reflect the complexity of a postpartum haemorrhage.…”
Section: Discussionsupporting
confidence: 90%
“…Haemorrhage after delivery remains one of the leading causes of postpartum maternal morbidity and mortality worldwide, 5 and blood loss after delivery is also a common indication for maternal red‐cell transfusion. Studies show an increased risk of recurrent blood loss in delivery in women with previous postpartum haemorrhage 6–9 . Although the mechanisms driving recurrent haemorrhage can be difficult to disentangle, it may be explained by the persistence of both endogenous and environmental predisposing factors 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antepartum model, which included demographic, pregnancy-related, and maternal comorbidities; and an intrapartum model, which included labor and delivery-related risk factors. The event rate of uterine atony was determined to be 16%, a figure consistent with other reports from the literature 4. As stated above, <1% of patient records contained a diagnostic code indicating a prior PPH.…”
Section: Commentsupporting
confidence: 85%
“…The event rate of uterine atony was determined to be 16%, a figure consistent with other reports from the literature. 4 As stated above, <1% of patient records contained a diagnostic code indicating a prior PPH. Multiple gestations was identified as a risk factor with an odds ratio (OR) > 2 in both models, while there was a negative association (OR <0.51) with a perineal laceration in the intrapartum model.…”
Section: Commentmentioning
confidence: 99%